Essential fatty acid metabolism and requirements of the cleaner fish, ballan wrasse Labrus bergylta: Defining pathways of long-chain polyunsaturated fatty acid biosynthesis - Kabeya, Naoki; Yevzelman, Simon; Oboh, Angela; Tocher, Douglas R; Monroig, Oscar (Aquaculture, 2018)
Ballan wrasse (Labrus bergylta) is an effective counter-measure against sea lice used by Atlantic salmon farmers, proving to be more effective and economical than drugs or chemical treatments alone. There are currently efforts underway to establish a robust culture system for this species, however, essential fatty acid dietary requirements are not known for ballan wrasse. In the present study, we isolated and functionally characterised ballan wrasse fatty acid desaturase (Fads) and elongation of very long-chain fatty acids (Elovl) protein to elucidate their long-chain polyunsaturated fatty acid (LC-PUFA) biosynthetic capability. Sequence and phylogenetic analysis demonstrated that the cloned genes were fads2 and elovl5 orthologues of other teleost species. Functional characterisations of fads2 and elovl5 were performed using the yeast (Saccharomyces cerevisiae) heterologous expression system. The Fads2 showed Δ6 desaturase activity towards 18:3n–3, 18:2n–6 and 24:5n–3, and Δ8 desaturase activity towards 20:3n–6 and 20:2n–6. The Elovl5 showed elongase activities towards various C18 and C20 fatty acids. Therefore, 20:4n–3 and 20:3n–6 can be synthesised from 18:3n–3 and 18:2n–6, respectively in ballan wrasse via two possible pathways, the Δ6 (Δ6 desaturation – elongation) and Δ8 (elongation – Δ8 desaturation) pathways. However, due to the absence of Δ5 desaturase activity and no other Fads2 in their genome, 20:5n–3 (eicosapentaenoic acid, EPA) and 20:4n–6 (arachidonic acid, ARA) cannot be synthesised from C18 PUFA precursors and they could consequently be regarded as dietary essential fatty acids for ballan wrasse. Since no Δ4 desaturase activity was detected in ballan wrasse Fads2, 22:6n–3 (docosahexaenoic acid, DHA) can only be synthesised from EPA via the Sprecher pathway comprising two sequential elongation steps to produce 24:5n–3 followed by Δ6 desaturation and chain shortening. Although ballan wrasse Elovl5 had no elongase activity towards C22, other elongases such as Elovl4 exist in the ballan wrasse genome ...